Levels, Temporal-Spatial Variations, and Sources of Organochlorine Pesticides in Ambient Air of Lake Chaohu, China - Hui-Ling Ouyang; Wei He; Ning Qin; Xiang-Zhen Kong; Wen-Xiu Liu; Qi-Shuang He; Qing-Mei Wang; Yu-Jiao Jiang; Chen Yang; Bin Yang; Fu-Liu Xu (The Scientific World Journal)
The residual levels of OCPs in the gas phase and particle phase in Lake Chaohu, China, were measured using GC-MS from March 2010 to February 2011. The temporal-spatial variations and sources of OCPs were also analyzed. Twenty types of OCPs were detected in the gas phase with a total concentration of 484.8±550.4 pg/m3. Endosulfan, DDTs and chlordane were the primary OCPs in the gas phase. The mean concentration of OCPs in the gas phase was significantly higher in the summer than in the winter. Seventeen types of OCPs were detected in the particle phase with a total concentration of 18.3 ± 26.1 pg/m3. DDTs were major OCPs in the particle phase. The mean concentration of OCPs in the particle phase decreased at first and then increased during the period. The potential source of the HCHs in ambient air of Lake Chaohu might come from recent lindane usage. DDTs mainly came from historical dicofol usage, and an input of DDT was observed in the spring, which may result from the present use of marine paint that contains technical DDT. Endosulfan and chlordane in the air may be due to the present use of technical endosulfan and chlordane.